2000
DOI: 10.1016/s0896-6273(00)80877-6
|View full text |Cite
|
Sign up to set email alerts
|

Rest in Drosophila Is a Sleep-like State

Abstract: To facilitate the genetic study of sleep, we documented that rest behavior in Drosophila melanogaster is a sleep-like state. The animals choose a preferred location, become immobile for periods of up to 157 min at a particular time in the circadian day, and are relatively unresponsive to sensory stimuli. Rest is affected by both homeostatic and circadian influences: when rest is prevented, the flies increasingly tend to rest despite stimulation and then exhibit a rest rebound. Drugs acting on a mammalian adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
919
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 947 publications
(1,030 citation statements)
references
References 33 publications
39
919
0
4
Order By: Relevance
“…This so-called crepuscular pattern of activity has been known since the early days -the very name Drosophila is Greek for "lover of the dew" -and the first systemic reports about the alternation of periods of activity and quiescence in adult Drosophila date back to 1956 1 . However, despite a long standing interest in the circadian regulation of Drosophila 50 activity, little was known about the biological characteristics of the mainly nocturnal resting state until the year 2000, when two independent laboratories demonstrated that the prolonged inactivity observed in Drosophila fully satisfies the five behavioural characteristics that define a sleep-like status 2 : (i) consolidated circadian periods of immobility, (ii) a species-specific posture and/or resting place, (iii) an increased arousal threshold, (iv) reversibility to wakefulness and (v) a 55 homeostatic regulatory mechanism 3,4 . We now know that sleep loss has similar detrimental effects on flies as it has on mammals 5,6 and that social experience modulates sleep need in Drosophila, as it does in vertebrates 7,8 .…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…This so-called crepuscular pattern of activity has been known since the early days -the very name Drosophila is Greek for "lover of the dew" -and the first systemic reports about the alternation of periods of activity and quiescence in adult Drosophila date back to 1956 1 . However, despite a long standing interest in the circadian regulation of Drosophila 50 activity, little was known about the biological characteristics of the mainly nocturnal resting state until the year 2000, when two independent laboratories demonstrated that the prolonged inactivity observed in Drosophila fully satisfies the five behavioural characteristics that define a sleep-like status 2 : (i) consolidated circadian periods of immobility, (ii) a species-specific posture and/or resting place, (iii) an increased arousal threshold, (iv) reversibility to wakefulness and (v) a 55 homeostatic regulatory mechanism 3,4 . We now know that sleep loss has similar detrimental effects on flies as it has on mammals 5,6 and that social experience modulates sleep need in Drosophila, as it does in vertebrates 7,8 .…”
Section: Overviewmentioning
confidence: 99%
“…Conservation of sleep from humans to flies extends beyond behaviour to pharmacology (e.g. : caffeine and amphetamines promote wakefulness 3,4 , whereas sedatives like hydroxyzine promote sleep 4 ) and flies, like vertebrates, show distinct electrophysiological correlates 60 of wakefulness and sleep in the brain neuronal activity 9 . Together, these findings demonstrate an evolutionary conservation between Drosophila and human sleep at the behavioural and molecular levels, making flies an ideal system to study the mysterious functions of sleep and all its connections to pathological conditions in humans.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) The first four clock genes identified are non-essential genes with few roles outside the clock. Indeed, they seem dedicated to rhythmic processes, as their other reported effects include altered courtship song rhythms and recovery from sleep deprivation [20,21]. This can be contrasted with the first two learning and memory genes identified in Drosophila, dunce and rutabaga, which are essential genes with general roles in cyclic AMP signal transduction [reviewed in 22].…”
Section: Circadian Rhythms In Drosophilamentioning
confidence: 99%